Exploration of Factors Related to Depressive Symptomatology in Family Members of Military Veterans With Traumatic Brain Injury. (May 2018) - Moriarty, Helene; Winter, Laraine; Short, Thomas H.; True, Gala
Traumatic brain injury (TBI) is a family affair, affecting those with the injury and their families. Psychological distress, often measured as depression or depressive symptoms, is highly prevalent among family members. Predictors of depression in family members of civilians with TBI have been examined, but predictors of depression in family members of military veterans have received very little research attention and are poorly understood. To address the knowledge gap, this study explored factors related to depressive symptoms in family members of veterans in the United States, using an ecological framework. Baseline data from 83 family members were used. Family members with higher caregiver burden, presence of a veteran with posttraumatic stress disorder (PTSD), and greater financial difficulty experienced significantly more depressive symptoms. Findings suggest that efforts to support family members and decrease their depression should aim to reduce caregiver burden and financial difficulty, and help family members cope with veteran PTSD and TBI. Family-focused interventions are needed.